Cardiovascular strain impairs prolonged self-paced exercise in the heat - Periard, J. D.; Cramer, M. N.; Chapman, P. G.; Caillaud, C.; Thompson, M. W. (Experimental Physiology, 2011)
It has been proposed that self-paced exercise in the heat is regulated by an anticipatory reduction in work rate based on the rate of heat storage. However, performance may be impaired by the development of hyperthermia and concomitant rise in cardiovascular strain increasing relative exercise intensity. This study evaluated the influence of thermal strain on cardiovascular function and power output during self-paced exercise in the heat. Eight endurance-trained cyclists performed a 40 km simulated time trial in hot (35°C) and thermoneutral conditions (20°C), while power output, mean arterial pressure, heart rate, oxygen uptake and cardiac output were measured. Time trial duration was 64.3 ± 2.8 min (242.1 W) in the hot condition and 59.8 ± 2.6 min (279.4 W) in the thermoneutral condition (P < 0.01). Power output in the heat was depressed from 20 min onwards compared with exercise in the thermoneutral condition (P < 0.05). Rectal temperature reached 39.8 ± 0.3 (hot) and 38.9 ± 0.2°C (thermoneutral; P < 0.01). From 10 min onwards, mean skin temperature was ~7.5°C higher in the heat, and skin blood flow was significantly elevated (P < 0.01). Heart rate was ~8 beats min-1 higher throughout hot exercise, while stroke volume, cardiac output and mean arterial pressure were significantly depressed compared with the thermoneutral condition (P < 0.05). Peak oxygen uptake measured during the final kilometre of exercise at maximal effort reached 77 (hot) and 95% (thermoneutral) of pre-experimental control values (P < 0.01). We conclude that a thermoregulatory-mediated rise in cardiovascular strain is associated with reductions in sustainable power output, peak oxygen uptake and maximal power output during prolonged, intense self-paced exercise in the heat.